Continuance Usage of Collaboration Tools after Social Distancing and The Influential Factors - Salsabila, Aulia Rido; Wilantika, Nori; Santoso, Ibnu; Choir, Achmad Syahrul (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2025)
Working from home (WFH) during the COVID-19 pandemic has challenges in terms of communication and coordination among employees due to the distance. Therefore, collaboration tools were needed during the COVID-19 pandemic. As we recover from the pandemic, the government revoked the social distancing policy restricting people's activities. The revoke is assumed to influence the continued use of collaboration tools. This study aims to understand the continuance usage of collaboration tools after no more social distancing. This study also seeks to identify the factors influencing the ongoing use of collaboration tools by integrating the Technology Acceptance Model (TAM) and Expectation Confirmatory Model (ECM). The method of data analysis employed was the partial least squares structural equation model (PLS-SEM). The findings indicated that most of 437 respondents kept using collaboration tools after no more social distancing. However, there was a decrease in the frequency of use. Our study findings have also proved that Actual Continued Usage is influenced by Continuance Intention by 43%. Furthermore, a factor that influences continuance intention the most is the attitude toward using collaboration tools. The results of this study also support the integration of TAM and ECM to examine user intentions and behavior regarding the continuance use of a technology.